Herpes zoster: Report of a treated case with review of literature - K Srikrishna; MPV Prabhat; Praveen Kumar Balmuri; S Sudhakar; D Ramaraju (Wolters Kluwer Medknow Publications, 2012)
Herpes zoster is a localized, generally painful cutaneous eruption that occurs most frequently among older adults and immunocompromized persons. It is caused by reactivation of latent varicella zoster virus (VZV) Approximately one in three persons will develop zoster during their lifetime. A common complication of zoster is postherpetic neuralgia (PHN), a chronic, often debilitating pain condition that can last months or even years. The risk for PHN in patients with zoster is 10 to 18%. Approximately 3% of patients with zoster are hospitalized. Death attributable to zoster are common among immunocompromized persons. Prompt treatment with the oral antiviral agents, corticosteroids and analgesics decreases the severity and duration of acute pain from zoster. This article reviews herpes zoster and reports one such case, which was treated successfully without any complications.